(untitled) (Fiep Bulletin - online, 2011)
The recent changes in Brazilian education, specifically targeted to high school, has required educators increasingly address the issue of interdisciplinarity. In the case of Physical Education, the challenge becomes greater by the existence of a paradigm that makes the teaching of this course is primarily aimed at sports or physical exercise. The aim of this paper is based on the topics of health and quality of life, propose changes in program content achievable Physical Education IFES. The proposed adjustment of the curriculum covered two phases, one to investigate the satisfaction of teachers of Physical Education of IFES, and the curricular structure of the discipline and at another time to verify the acceptance of this theme of "health" in the syllabus . The results show that over 65% of teachers are partially satisfied with the curriculum structure of discipline and 100% approved the inclusion of health in their subject content through a practical approach - theoretical.